Zeitschrift für Wirtschaftsgeographie : The German Journal of Economic Geography (De Gruyter, 1982)
The primary focus of the German Journal for Economic Geography (ZFW) is on theory-led empirical research about spatial economic structures and regional dynamics. ZFW, which is the only scientific journal on Economic Geography in German speaking countries, addresses scientists and students as well as decision makers in private firms and economic promotion agencies.